2019
DOI: 10.1111/1440-1681.13052
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of cathepsin D protects dopaminergic neurons against neuroinflammation‐mediated neurotoxicity through inhibition of NF‐κB signalling pathway in Parkinson's disease model

Abstract: Additional supporting information may be found online in the Supporting Information section at the end of the article.How to cite this article: Gan P, Xia Q, Hang G, et al. Knockdown of cathepsin D protects dopaminergic neuronsagainst neuroinflammation-mediated neurotoxicity through inhibition of NF-κB signalling pathway in Parkinson's disease model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Therefore, it appears likely that the upregulation of pro-inflammatory cytokines seen in our study after pharmacological inhibition of cathepsin B, S, and L is also at least in part due to compensatory upregulation of various other cathepsins, such as cathepsin D, known to contribute to the development and maintenance of a pro-inflammatory M1-like phenotype [84,85]. In this context, knockout experiments in murine primary microglia cells have demonstrated that cathepsin D plays an important role in the activation of NF k B-mediated signaling pathways [86]. Another cathepsin family member warranting investigation in this context is cathepsin C. Strong expression of cathepsin C was detected in murine M1 macrophages and seems to be important for M1 polarization status.…”
Section: Discussionsupporting
confidence: 50%
“…Therefore, it appears likely that the upregulation of pro-inflammatory cytokines seen in our study after pharmacological inhibition of cathepsin B, S, and L is also at least in part due to compensatory upregulation of various other cathepsins, such as cathepsin D, known to contribute to the development and maintenance of a pro-inflammatory M1-like phenotype [84,85]. In this context, knockout experiments in murine primary microglia cells have demonstrated that cathepsin D plays an important role in the activation of NF k B-mediated signaling pathways [86]. Another cathepsin family member warranting investigation in this context is cathepsin C. Strong expression of cathepsin C was detected in murine M1 macrophages and seems to be important for M1 polarization status.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, CathD was also found to be up-regulated in the activated microglia (Takenouchi et al, 2011;Yelamanchili et al, 2011), the increased level of which can cause neuronal death (Amritraj et al, 2013). Our previous study reported that CathD was significantly up-regulated in MPTP-induced PD mice in vivo and in LPS-induced mice primary microglia in vitro, and that knockdown of CathD inhibited neuroinflammation and protected DA neurons from microglia-mediated neurotoxicity via inhibiting the activation of NF-kB signaling pathway (Gan et al, 2018). Therefore, CathD not only participates in the neuroinflammatory responses, but also trigger neurodegeneration and possibly development of neurodegenerative disorders including PD.…”
Section: Discussionmentioning
confidence: 97%
“…Overloaded IL‐1β, IL‐6, and TNF‐α act on adjacent microglia to induce neuroinflammation and glia‐activated feedback loops which aggravates the production of neurotoxic molecules 34 . In addition, excessive NO inhibits mitochondrial cytochrome oxidase, which results in neuronal apoptosis 35 36 .…”
Section: Discussionmentioning
confidence: 99%